"We do not dare to love": women with disabilities' sexual and reproductive health and rights in rural Cambodia. Issue 50 (12th June 2017) - Gartrell, Alexandra; Baesel, Klaus; Becker, Cornelia
Abstract: There is an urgent need for an evidence base to inform the implementation of disability inclusive sexual and reproductive health (SRH) policy and programming to address women with disabilities' largely unattained SRH rights. This paper presents findings from a qualitative study on the sexual and reproductive health and rights (SRHR) of women with disabilities in rural Cambodia. The findings highlight three critical steps to enhance the physical, communicative and financial accessibility of SRHR information and services. Firstly, strengthen women with disabilities' economic livelihoods, social and financial resources, and thereby, their capacity to make and act on their own SRHR decisions. Secondly, engage women with disabilities as community role models and advocates who actively provide input into health service decision-making, planning and delivery. Thirdly, ensure health centre staff have access to communication resources and aids to strengthen their skills to communicate with women with hearing impairments. Together these steps will support women with disabilities to claim their sexual and reproductive rights and transform the social attitudes of persons in the lives of women with disabilities, including health care staff.